FOMO, Materialism and the Gen Z Shopping Behavior: The Impact on Online Impulse Buying and Post-Purchase Regret (With a Gender Perspective) - Charles, Clivyne Eugenia; Immanuel, Dewi Mustikasari (Universitas Brawijaya, Indonesia, 2025)
Online buying patterns have changed dramatically as e-commerce, especially among Generation Z, and the growing influence of digital revolutions rapidly rise. Studies indicate that 72% of Indonesian Gen Z consumers prefer Shopee due to its personalized promotions and interactive shopping features. The urgency of this study results from the growing awareness that materialism and psychological elements like Fear of Missing Out (FOMO) significantly affect impulsive buying decisions, which frequently cause post-purchase dissonance. Given Gen Z's predominance in online purchasing and their significant exposure to digital promotions, it is imperative to investigate the underlying psychological factors behind impulse buying and consequent regret. This study analyzes the effect of FOMO and Materialism on online impulsive buying and post-purchase dissonance, taking gender as the moderating variable. Using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to examine responses from 444 Gen Z consumers in Indonesia, chosen via purposive sampling, the study takes a quantitative approach. To offer a relevant and contextualized study, the paper centers on Shopee, one of the top e-commerce systems in Indonesia. It is observed that R² explains 62.6% of online impulse buying and 27.1% of post-purchase dissonance, hence showing that the strength of the model is good. The findings support the fact that FOMO and materialism have a significant influence on online impulse buying, which then leads to post-purchase dissonance. Online impulse buying also acts as a mediator, enhancing the effect of FOMO and materialism on post-purchase dissonance. This study did not find any appreciable influence of gender in these interactions. Practical implications are that strategic marketing efforts must be developed to manage consumer expectations and minimize dissonance by offering better post-purchase support systems.